The many facets of privately negotiated stock repurchases - Peyer, Urs C.; Vermaelen, Theo (Journal of Financial Economics, 2005)
We investigate the causes and consequences of 737 privately negotiated share repurchases in the years 1984–2001. In contrast to the negative announcement returns and positive repurchase premiums reported by past research, we find positive announcement returns and premiums that are not significantly different from zero. Only when we investigate the 60 greenmail events separately do we find results similar to past research. However, for this subsample, we find long-horizon excess returns that are comparable to the average 18% repurchase premium, challenging the widely accepted opinion that managers overpay in greenmail repurchases. Moreover, we find that our understanding of the event improves when we split the non-greenmail repurchases according to the price paid. Repurchases at a premium can be modeled as signals, while other repurchases are mere wealth transfers between the corporation and the selling stockholders, the extent of which is determined by the relative bargaining power of the seller and the repurchasing firm.